ACID SENSING ION CHANNELS (ASICS): POTENTIAL TARGETS FOR THE DISCOVERY OF NOVEL THERAPEUTICS IN DISEASE MANAGEMENT - Roy, Debendra Nath (International Journal of Clinical and Biomedical Research, 2018)
Acid sensing ion channels (ASIC) are Na+ channels activated by external protons. Number of neurological (pathological pain, expression of fear, anxiety, depression, and neurodegeneration after ischemic stroke etc) and non -neurological (brain tumor, cardiovascular mechanosensation, hypoxia induced hypertension, glaucoma, etc.) disorders are implicated by various ASICs subtypes. Due to heir known and potential roles in many disease pathologies, it is very authentic to explore the importance of new and selective small molecule inhibitors and even activators of ASICs as a research tool in clinical uses for treating these diseases pathogenesis. This review is aimed to find out the therapeutic potentialities of ASICs argeed novel drugs in contex of their pathophysiological role in human body. Fluorescent dyes and optical sensors as a means of fast and efficient screening approaches would certainly be used to improve he discovery technology of ASICs modulated drugs.